(untitled) (MIST International Journal of Science and Technology, 2025)
Stainless steel (SS) is becoming increasingly popular as reinforcement across the globe, owing to its superior mechanical and durability properties. This study numerically investigates the flexural behavior of concrete beams reinforced with stainless steel. Primarily, the experimental results are validated by developing 3D finite element (FE) models with stainless steel rebars, considering the actual test data. In the modelling process, 8-node brick element for concrete and 2-node beam element for reinforcement were employed in the finite element model. The numerical results are presented in terms of load displacement response, yield, and ultimate capacity with respective deformation, ductility, etc. The numerical results depicted reasonably good precision in predicting the load deformation response and ultimate load of the concrete beam reinforced with stainless-steel. The models have been regenerated for concrete beams with conventional mild steel to investigate the comparative behaviour in terms of significant changes in their load-carrying capacity and the corresponding ultimate deformation. Results revealed that the peak loads remained approximately the same for 30 MPa and 40 MPa concrete strengths, although the stainless-steel reinforced beams showed greater deformability and ductility. In addition, a parametric study of reinforced concrete beam models consisting of Grade 201 stainless steel rebars and 60-grade mild steel rebars with varying concrete grades of 30 MPa, 40 MPa, and 50 MPa was also performed to inspect their influence on the initial stiffness, ductility, and ultimate load-carrying capability of the concrete beams. The numerical response rendered that beams reinforced with stainless steel provide similar ultimate flexural capacity with improved stiffness and ductility in contrast to that of the mild steel rebars. MIJST, V. 13,December 2025: 39-46 https://doi.org/10.47981/j.mijst.13(02)2025.570(39-46)